Frequency of otitis media with effusion among children aged 1–5 years presenting to immunization center of tertiary care hospitals, Rawalpindi. Issue 4 (16th May 2022) - Riaz, Nida; Ajmal, Muhammad; Khan, Muhammad Sheharyar
Abstract: Objective: We conducted this study to assess the etiopathogenic relation of otitis media with effusion (OME) in a group of children aged 1–5 years among the local population of Rawalpindi. Methods: This was a cross‐sectional retrospective study. Study was conducted among the children presenting to the immunization center of three tertiary care hospitals of Rawalpindi. Otitis media was assessed by clinical examination and tympanometry from August 2019 to January 2020. Multi‐factor regression analysis was then applied to recognize the statistical significance and association of various risk factors to OME. Results: Out of 400 children enrolled in this study, 108 (27.0%) had OME, out of which 65 (60.2%) were males and 30 (27.8%) were of age group 2–3 years. Multivariable regression analysis of risk factors associated with OME showed it was strongly associated with snoring ( P  < 0.001), last year symptoms (attack of ear aches with hearing loss [ P  = 0.002]), drugs (URTI antibiotics [ P  = 0.026], All 3 drugs [ P  = 0.013]). Conclusions: We found out that OME is a common disease which if not identified or treated timely can lead to other hard to cure health problems. Control of its etiopathogenic factors can play a major role in its prevention.